Antipsychotic activity of standardized Bacopa extract against ketamine-induced experimental psychosis in mice: Evidence for the involvement of dopaminergic, serotonergic, and cholinergic systems. (December 2015) - Chatterjee, Manavi; Verma, Rajkumar; Kumari, Reena; Singh, Seema; Verma, Anil Kumar; Dwivedi, Anil Kumar; Palit, Gautam
Abstract Context: Schizophrenia is a chronic disabling psychiatric disorder affecting 1% of the population worldwide. Due to the adverse effects of available antipsychotic medications, recent investigations have focused on the search for well-tolerated, safe molecules from natural resources to control the severity and progression of schizophrenia. Objective: To screen the standardized extract of Bacopa monniera Linn. (Scrophulariaceae) (BM) for its antipsychotic potential in the ketamine-induced psychosis model with mice. Materials and methods: Graded dose of BM (40, 80, and 120 mg/kg, p.o.) were given to the mice 1 h prior to ketamine administration and tested for positive symptoms and cognitive deficits. A chronic ketamine treatment regimen was used to study the effect of BM on negative symptoms such as immobility enhancement. Each mouse was used once for the behavioral studies. Results: BM reduced ketamine-induced hyperactivity with an EC50 value of 76.60 mg/kg. The 80 mg/kg dose was used for all other behavior analysis. Pretreatment with BM at 80 mg/kg showed two-fold increases in transfer latency time (TLT) in passive avoidance task. Chronic BM pretreatment (80 mg/kg p.o. daily × 10 d) ameliorated the ketamine-induced enhanced immobility effect by 21% in the forced swim test. BM treatment reversed ketamine-induced increase in monoamine oxidase activity in both cortex and striatum and normalized the acetylcholinesterase activity and the glutamate levels in the hippocampus. Discussion and conclusion: Overall our findings suggest that BM possesses antipsychotic properties which might be due to its modulatory action on dopamine, serotonin, and glutamate neurotransmission.